Nuevos aportes sobre la avifauna de la provincia de Santiago del Estero, Argentina - Coria, Oscar R.; Gómez, Norberto; Heredia, Javier; Quiroga, Oscar; Carrizo, Daniel A.; Ruiz, Pablo; Herrera, Martín; Rojas, Lilia M. (Nuestras Aves, 2013)
Este artículo no cuenta con un resumen.